Peningkatan Kesadaran Toleransi Antar Umat Beragama Melalui Program Sosialisasi Di Lingkungan Kelas XII MA Ma'arif Cepogo Boyolali - Chorrie Elysa Gurning; Chanda Anindita Putri; Daffa Andhika Yudistira; Danang Apriyanto; Aris Budi Prasetyo (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to increase the understanding and awareness of 12th-grade students at MA Ma’arif Cepogo regarding the importance of interfaith tolerance. The lack of understanding of tolerance in the school environment necessitates systematic efforts through targeted education. Implementation methods included initial direct observation to determine the condition and level of student understanding, outreach using a two-way communication approach to actively engage participants, and documentation of the activity through photos and videos. Additionally, a quiz was administered as an evaluation to measure improvements in student knowledge and engagement. The results of the activity showed an increase in student understanding of the concept of tolerance, reflected in enthusiasm during discussion sessions and improved quiz scores. This program can serve as a model for character education for schools in building an inclusive and harmonious environment.